Republic of Chile : Country Financial Accountability Assessment - World Bank (Washington, DC, 2012)
Chile's macroeconomic policies and strong fundamentals have, to a large extent, insulated it from regional crises, and have allowed continued growth in recent years, albeit at lower rates than in the mid-1990s. Economic performance continues to outpace that of the rest of the Region, and in per capita terms, GDP growth has averaged 4 percent per year since 1990, versus one percent for the Latin America and the Caribbean (LAC) region during the same period. This performance is sustained by sound policies and an ambitious structural reform agenda. The abundant trust in government in Chile today, can be attributed, in part, to two elements of transparency: its fiscal reporting, and the incontestable review by a competent, independent authority - the CGR (Controller General of the Republic). Furthermore, Chile has effectively centralized policies and procedures to support aggregate fiscal discipline, yet, its public financial management is characterized by a unique blend of strengths and weakness. Chile is well into the second generation of public sector reforms. Notwithstanding the favorable status of financial management, to advance with modernization in terms of fiscal transparency, several issues have to be addressed. For Chile to emerge at the forefront of public sector management, it should issue its annual financial statements with an audit opinion, adherent with international accounting standards. But to render opinions, the CGR would have to distance itself from both the ex ante approval role of budget uses, and the preparation of the annual financial statements. Thus, the authorities should consider a solution that complies with international practices, and accommodates with country constraints.